UJI ADAPTASI BERBAGAI GENOTIPE KACANG TANAH DI KOMPOSISI MEDIA TANAM TAILING - Afrizal Muchtadin; Eries Dyah Mustikarini; Gigih Ibnu Prayoga (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
Groundnut are protein-producing plants that humans need. ground nut production in Bangka Belitung is still low. Efforts to increase groundnut production can be done by utilizing post-tin mining land. The research was conducted at the research experiment gardens University of Bangka Belitung. The purpose of this research is to find the groundnut genotype that is able to adapt to the tailings media. The research design used was Factorial Randomized Block Design (FRBD) consisting of 2 factors. Factor 1 are the genotypes of Jongkong, Belimbing, Air Ketimbai 1, Air Ketimbai 2, Hypoma 1 and Talam 2. Factor 2, which is the composition of 100% ultisol planting media, 100% tailings, 70% tailings + 30% ultisol and 50% + tailings ultisol 50%. The results of this study indicate that groundnut genotypes that have a high level of adaptation are Jongkong on the character of plant height, number of leaves, root volume, number of pods per plant, and number of filled pods per plant. National varieties that have a high level of adaptation are Talam 2 and Hypoma 1 on the character of plant height, canopy wet weight, weighted weight, root volume and number of filled pods per plant. Jongkong accession, Hypoma 1 and Talam 2 varieties can be recommended as groundnut plants for cultivation on tailings land.